The Importance of Early Childhood Education in Building Social and Emotional Intelligence in Children - Imam Tabroni; Dian Hardianty; Rini Purnama Sari (Jurnal Multidisiplin Madani, 2022)
This research is motivated by the presence of many people who have a high level of intelligence, but are less able to realize success in their lives, this is caused by social and emotional intelligence factors, not a few people who are less able to control impulses , are less able to manage stress with good, also less able to communicate well and less able to recognize and solve problems, and less able to adapt and so on. Seeing this, it is necessary to conduct a study of this incident by taking samples from various examples in the community who are currently or have undergone the process of educating their children. Researchers conducted surveys and asked questions with people around and got various kinds of responses that were quite diverse. To achieve this goal, this research uses qualitative-descriptive research methods with literature study techniques. The results of this study obtained data and facts that early childhood education () is very important in providing a stimulus in growing hidden potentials in children, namely the dimensions of child development, and one of them is social emotional development in early childhood.